Functional Properties of the Processing Soybeans Products (Eurasian Research Bulletin, 2022)
Some functional properties can be interpreted as a result of the thermodynamically favorable protein-water interactions (wettability, swelling, water retention, solubility) or unfavorable (foaming, emulsification). The interactions of protein with water are important in relation to dispensability, water absorption and binding, swelling, viscosity, gelation and surfactant properties as these properties influence the important functions of proteins in meat, bakery and beverage systems. Ease of dispensability or wettability is important in food formulations and is affected by surface polarity, topography, texture and area, and by the size and microstructure of the protein particles. Bound water includes all hydration water and some water loosely associated with protein molecules following centrifugation, ranging from 30 to 50 g per 100 g protein